A 13-Steroid Serum Panel Based on LC-MS/MS: Use in Detection of Adrenocortical Carcinoma. (1st December 2017) - Taylor, David R; Ghataore, Lea; Couchman, Lewis; Vincent, Royce P; Whitelaw, Ben; Lewis, Dylan; Diaz-Cano, Salvador; Galata, Gabriele; Schulte, Klaus-Martin; Aylwin, Simon; Taylor, Norman F
Abstract: BACKGROUND: Adrenocortical carcinoma (ACC) is a rare malignancy, with an annual incidence of 1 or 2 cases per million. Biochemical diagnosis is challenging because up to two-thirds of the carcinomas are biochemically silent, resulting from de facto enzyme deficiencies in steroid hormone biosynthesis. Urine steroid profiling by GC-MS is an effective diagnostic test for ACC because of its capacity to detect and quantify the increased metabolites of steroid pathway synthetic intermediates. Corresponding serum assays for most steroid pathway intermediates are usually unavailable because of low demand or lack of immunoassay specificity. Serum steroid analysis by LC-MS/MS is increasingly replacing immunoassay, in particular for steroids most subject to cross-reaction. METHODS: We developed an LC-MS/MS method for the measurement of serum androstenedione, corticosterone, cortisol, cortisone, 11-deoxycorticosterone, 11-deoxycortisol, 21-deoxycortisol, dehydroepiandrosterone sulfate, pregnenolone, 17-hydroxypregnenolone, progesterone, 17-hydroxyprogesterone, and testosterone. Assay value in discriminating ACC from other adrenal lesions (phaeochromocytoma/paraganglioma, cortisol-producing adenoma, and lesions demonstrating no hormonal excess) was then investigated. RESULTS: In ACC cases, between 4 and 7 steroids were increased (median = 6), and in the non-ACC groups, up to 2 steroids were increased. 11-Deoxycortisol was markedly increased in all cases of ACC. All steroids except testosterone in males and corticosterone and cortisone in both sexes were of use in discriminating ACC from non-ACC adrenal lesions. CONCLUSIONS: Serum steroid paneling by LC-MS/MS is useful for diagnosing ACC by combining the measurement of steroid hormones and their precursors in a single analysis.